2017
DOI: 10.1136/gutjnl-2016-312223
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence and mortality risks in a large US Barrett's oesophagus cohort

Abstract: Patients with BE had a persistent excess risk of oesophageal adenocarcinoma over time, although their absolute excess risks for this cancer, any cancer and overall mortality were modest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 31 publications
(55 reference statements)
2
21
1
4
Order By: Relevance
“…The study was an extension of a previous report by the same group and used the same data sources . Its findings accord with at least five nonpopulation‐based studies . In contrast with the present study, the UK study did not report an increased risk of cardiovascular death among patients with Barrett's oesophagus.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The study was an extension of a previous report by the same group and used the same data sources . Its findings accord with at least five nonpopulation‐based studies . In contrast with the present study, the UK study did not report an increased risk of cardiovascular death among patients with Barrett's oesophagus.…”
Section: Discussionsupporting
confidence: 79%
“…Barrett's oesophagus is a pre‐malignant condition of the distal oesophagus characterised by replacement of normal squamous epithelium with columnar epithelium . Several recent studies have indicated that patients with Barrett's oesophagus have higher mortality than the general population, but that death due to oesophageal malignancy is not the primary underlying cause . This is consistent with the finding that the annual malignant transformation rate in Barrett's oesophagus is approximately 0.2% .…”
Section: Introductionsupporting
confidence: 82%
“…5 The only known potential precursor of EA/EGJA is Barrett's esophagus (BE), which is associated with a 10-times Cancer December 1, 2019 to 40-times increased risk of EA/EGJA. [6][7][8] Among individuals older than 50 years with gastroesophageal reflux disease (GERD), an estimated 10% also have BE. 9 In the last 30 years, BE diagnosis increased 200% to 300%, independent of the number of gastrointestinal endoscopies performed.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, as the efficacy of surveillance on reducing mortality of patients with BE compared with the general population is unclear, the value of ongoing surveillance for patients with NDBE is debated. 7,8 In addition, as the absolute risk of malignant progression in patients with NDBE is low (<0.5%/year), the majority of patients with NDBE will never progress beyond NDBE or LGD and will only experience the disadvantages of the surveillance program. 9,10 Therefore, it would be helpful to identify patients at low risk of malignant progression, as in these patients surveillance intervals might be lengthened or even discontinued.…”
mentioning
confidence: 99%